The Gig Economy and Worker Stress : A Review of Literature in the Indian Context - Sapna Shekhawat; Dr. Swati Saxena (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The dynamic labor market of today, fueled by digital platforms, gives rise to a brand-new type of work known as the "Gig Economy." The Gig Economy offers unprecedented degrees of flexibility, autonomy, and freedom, but it also carries risks because there is little regulation and security. This research investigates the impact of demographic characteristics on the stress level of gig workers. This paper offers a comprehensive review of stress factors among gig workers in India, drawing insights from recent research. Nine research papers have been designated as key references for this study. Key stressors identified encompass demographic elements such as gender, income levels, working hours, and educational backgrounds. Other stress causing components were financial instability stemming from irregular income, pervasive job insecurity, unpredictable work schedules, and the blurring of boundaries between professional responsibilities and personal life. Recognizing and addressing these stressors are pivotal for safeguarding the holistic well-being and productivity of gig workers in the Indian context. The discerned insights furnish invaluable guidance for policymakers, employers, and researchers vested in alleviating the detrimental impacts of stress within the burgeoning gig economy.